NOX2 as a Biomarker of Academic Performance: Evidence from University Students during Examination - Cristina Nocella; Alessandra D'Amico; Roberto Cangemi; Chiara Fossati; Fabio Pigozzi; Elena Mannacio; Vittoria Cammisotto; Simona Bartimoccia; Valentina Castellani; Gianmarco Sarto; Beatrice Simeone; Erica Rocco; et al. (MDPI AG, 2024)
Background: Cortisol levels, oxidative stress, and lower cerebral performance seem to be closely related. This study aimed to evaluate the question of whether exam stress affected oxidative stress and endothelial function parameters in the salivary samples of students. Methods: A total of 114 healthy students were recruited. All students were subjected to a 21-item DASS questionnaire to assess perceived stress. Cortisol levels, biomarkers of oxidative stress, and endothelial function were evaluated at T0, during the semester, and T1, in the morning before the exam, in saliva samples. In vitro, HUVECs were stimulated with cortisol, and oxidative stress and endothelial function parameters were evaluated. Results: At T1, cortisol levels were significantly increased compared with the levels during the semester. Moreover, exam results correlated inversely with the DASS score at T1. In addition, NOX2, H2O2 and endothelin-1 significantly increased, while NO bioavailability decreased. In vitro, HUVECs treatment with human cortisol determined the increase of oxidative stress and the decrease of endothelial function, in association with impaired eNOS phosphorylation. Conclusion: NOX2-mediated oxidative stress is a mechanism that could mediate cortisol-induced transient endothelial dysfunction during academic examination. Therefore, strategies to monitor or modulate oxidative stress could help students to reduce the impact of examination-related stress.